2018
DOI: 10.1039/c8tc01315b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the key role of fluorine in improving the charge mobility of electron acceptors for non-fullerene organic solar cells by multiscale simulations

Abstract: F–π interactions play a key role in improving the electron mobility of fluorinated electron acceptors for non-fullerene OSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…The electron mobilities of ITOIC-2F, BFT-3D, and BFTT-3D amorphous thin lms were evaluated by a multiscale simulation based on quantum chemical calculations, molecular dynamics (MD) simulations, and Monte Carlo (MC) calculations, as detailed simulation processes were described in our previous works. 43,52,53 The geometry of ITOIC-2F, BFT-3D, and BFTT-3D are optimized using the quantum chemical calculations as mentioned above. Gromacs 5.1.4 molecular dynamic (MD) simulation package 54 is used to accomplish the MD simulations for all systems.…”
Section: Multiscale Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The electron mobilities of ITOIC-2F, BFT-3D, and BFTT-3D amorphous thin lms were evaluated by a multiscale simulation based on quantum chemical calculations, molecular dynamics (MD) simulations, and Monte Carlo (MC) calculations, as detailed simulation processes were described in our previous works. 43,52,53 The geometry of ITOIC-2F, BFT-3D, and BFTT-3D are optimized using the quantum chemical calculations as mentioned above. Gromacs 5.1.4 molecular dynamic (MD) simulation package 54 is used to accomplish the MD simulations for all systems.…”
Section: Multiscale Simulationsmentioning
confidence: 99%
“…In our previous work, we demonstrated that uorination can effectively inverse the electrostatic potential and produce intermolecular F-p interactions to improve electron mobilities in the ITOIC-2F amorphous lm. 43 Therefore, we utilized di-uorinated 1,1-dicyanomethylene-3-indanone as the electronwithdrawing end groups to construct new FREAs. To break the inherent planar structural characteristics of most existing FREAs, which may reduce the degree of phase separation, we used a central triptycene hub as a core structure to design threebladed propeller-shaped FREAs.…”
Section: Molecular Design and Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of the PHOLEDs employ unipolar host materials, which results in moderate charge transportation and inferior recombination efficiency. To overcome this issue, hosts with bipolar nature with high E T are more desirable . Until now, the most successful strategy for the development of bipolar host material is to combine the donor (D) and acceptor (A) units in order to achieve a broad recombination zone and balanced charge in emitting layer (EML), which could result in the high performance, that is highly sought after .…”
Section: Introductionmentioning
confidence: 99%